2003
DOI: 10.1097/01.tp.0000048488.35010.95
|View full text |Cite
|
Sign up to set email alerts
|

Migration of mesenchymal stem cells to heart allografts during chronic rejection

Abstract: MSC vigorously migrated into the site of allograft rejection. This data suggests that they may be attracted to this site to actively participate in tissue repair during chronic rejection. In addition, given the robust migration, the inhibition of MSC differentiation toward fibroblast progeny and induction toward the myocyte lineage may serve as a new strategy for treatment of chronic rejection and allograft tissue repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
120
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(126 citation statements)
references
References 24 publications
1
120
0
5
Order By: Relevance
“…Successful systemic delivery of MSC is dependent upon efficient homing of the cells to the required site. In this respect, the migration of MSC from the circulation into damaged or pathological tissues leading to therapeutic effects has been documented (Chen et al, 2001;Horwitz et al, 2002;Ortiz et al, 2003;Wu et al, 2003). More importantly, these studies documented the absence of non-specific trafficking of MSC to undamaged tissue, i.e.…”
Section: Methods Of Therapeutic Administration Of Mscmentioning
confidence: 88%
See 1 more Smart Citation
“…Successful systemic delivery of MSC is dependent upon efficient homing of the cells to the required site. In this respect, the migration of MSC from the circulation into damaged or pathological tissues leading to therapeutic effects has been documented (Chen et al, 2001;Horwitz et al, 2002;Ortiz et al, 2003;Wu et al, 2003). More importantly, these studies documented the absence of non-specific trafficking of MSC to undamaged tissue, i.e.…”
Section: Methods Of Therapeutic Administration Of Mscmentioning
confidence: 88%
“…Wang et al (2006), on the other hand, reported a reduction in the circulating pool of MSC in patients 1-week after MI and suggested that the MSC may have been recruited to the damaged myocardium. There are also several reports of the derivation of MSC from circulating fetal blood or umbilical cord (Ye et al, 1994;Campagnoli et al, 2000Campagnoli et al, , 2001Erices et al, 2000), and of the presence of MSC in the peripheral blood of other species (Huss et al, 2000;Wu et al, 2003). The two studies by Mansilla et al (2006) and Wang et al (2006) suggest that injury/trauma might evoke the release of MSC; thus systemic administration of MSC might enhance the presence of the circulating MSC, which may ultimately lead to an enhanced therapeutic response if the cells can be efficiently targeted to the damaged tissues.…”
Section: Do Msc Occur Naturally In the Blood?mentioning
confidence: 99%
“…In most forms of chronic vascular damage and repair, MSC home to and accumulate at sites where other cell types are actively dying [24,25,[52][53][54]. In chronic rejection, T-cell-dependent and antibody responses target the endothelium, contributing to a sustained increase in endothelial apoptosis [6][7][8][9][10][11][12]55].…”
Section: Discussionmentioning
confidence: 99%
“…It has been discovered in allograft studies conducted with rats that MSCs immigrate to the area of rejection and settle there after infusion [16]. MSCs are found to have improved the intestinal damage in studies concerning inflammatory bowel disease [17].…”
Section: Discussionmentioning
confidence: 99%